2016
DOI: 10.3329/bccj.v4i2.30025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance Pattern of Blood Isolates in Patients of Septicemia in ICU: Single Centre Observation

Abstract: Background: Septicaemia in critically ill patients is a life threatening condition and requires rapid antimicrobial treatment. Infections caused by drug-resistant organisms are more likely to increase risk of death in these patients. The present study was aimed to study the profile of organisms causing septicaemia and their antibiotic resistance pattern in an intensive care unit (ICU) of a teaching hospital in Bangladesh.Materials and Methods: This cross-sectional study was done in a 21-beded adult ICU of Dhak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
2
5
1
Order By: Relevance
“…In the present study, it was observed that E coli showed >65% resistance to Ampicillin, Ciprofloxacin, Trimethoprim-sulfamethoxazole and Amoxicillin /clavulanic acid (55.6%) similar to the results obtained by Ahsan et al, 24 (>80% ) in which maximum resistance among E coli was seen for Ciprofloxacin and third-generation Cephalosporins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, it was observed that E coli showed >65% resistance to Ampicillin, Ciprofloxacin, Trimethoprim-sulfamethoxazole and Amoxicillin /clavulanic acid (55.6%) similar to the results obtained by Ahsan et al, 24 (>80% ) in which maximum resistance among E coli was seen for Ciprofloxacin and third-generation Cephalosporins.…”
Section: Discussionsupporting
confidence: 91%
“…In the study, Acinetobacter TA B L E 2 (Continued) baumannii showed MDR more than 55% resistance to Penicillins, Cephalosporins, Carbapenems and Fluoroquinolones. A similar study carried out somewhere else by Ahsan et al 24 and Annamalei et al, 3 also yielded the same results where they observed >75% resistance to colistin. In the present study, it was found that CONS showed the highest resistance to Benzylpenicillin (84.4%), Erythromycin (69.2%) and Oxacillin (58.8%), which was observed to be similar to the results obtained from studies carried out by Mohanty et al, 10 (75%) and Khosravi et al, 26 (70.6%) showing high resistance to Penicillin.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Publication year 2004-2010 11 (23.9) (Arifeen et al, 2009;Brooks et al, 2005;Haque and Salam, 2010;Khan et al, 2004;Mahbubur et al, 2007;Monjur et al, 2010;Nahar et al, 2004;Rahman et al, 2005;Saha et al, 2009;Shahriar et al, 2010;Shill et al, 2010Shill et al, ) 2011Shill et al, -2014 14 (30.4) (Afroz et al, 2014;Ahmed et al, 2011Ahmed et al, , 2014Akram et al, 2014;Akter et al, 2014;Begum et al, 2013;Chiou et al, 2014;Dutta et al, 2013;Haque et al, 2011;Hossain et al, 2014;Islam et al, 2014;Khan et al, 2013;Rahman et al, 2014;Ud-Din et al, 2013-2018 21 (45.7) (Aftab et al, 2016;Ahmed et al, 2017Ahmed et al, , 2018Ahsan et al, 2016;Akter et al, 2016Akter et al, , 2017Begum et al, 2016;Chakraborty et al, 2016;Chowdhury and Parial, 2015;Haque et al, 2015;Hasan et al, 2016;Islam and Shamsuzzaman, 2015;Jobayer et al, 2017;Khanam et al, 2015;Nazme et al, 2017;…”
Section: Characteristicsmentioning
confidence: 99%
“…Community-acquired 5 (10.9) (Akter et al, 2014;Arifeen et al, 2009;Brooks et al, 2005;Mahbubur et al, 2007; (Aftab et al, 2016;Chiou et al, 2014;Hasan et al, 2016;Islam and Shamsuzzaman, 2015;Nahar et al, 2004;Rahman et al, 2014;Suchi et al, 2017) E-test 5 (10.9) (Arifeen et al, 2009;Begum et al, 2016;Khan et al, 2013;Mahbubur et al, 2007;Saha et al, 2009) Did not mention 5 (10.9) (Ahmed et al, 2018;Akram et al, 2014;Islam et al, 2014;Nazme et al, 2017;Shill et al, (Akter et al, 2016;Chowdhury and Parial, 2015;Haque et al, 2015;Khan et al, 2013;Nazme et al, 2017;Rahman et al, 2014;Saha et al, 2015;Shill et al, 2010;Suchi et al, 2017;Yasmeen et al, 2015) Bloodstream infection 7 (15.2) (Afroz et al, 2014;Ahmed et al, 2017Ahmed et al, , 2018Ahsan et al, 2016;Brooks et al, 2005;Khanam et al, 2015;Monjur et al, 2010) Gastroenteritis 8 (17.4) (Ahmed et al, 2011(Ahmed et al, , 2014Akter et al, 2017;Begum et al, 2016;Khan et al, 2004;…”
Section: Source Of Infectionmentioning
confidence: 99%